'We need to talk about your assignment': The requirements of procedural fairness when academic misconduct is first suspected - Evans, Michelle; Levine, Pnina (2017)
The credibility of Australian universities and their degrees recently came under national and international scrutiny in the wake of contract cheating scandals where students purchased assignments from internet websites, including the ‘MyMaster’ website. As well as threatening the reputation of universities, findings (and even allegations) of academic misconduct can have serious detrimental implications for students whose future careers and livelihoods may be jeopardised. This paper makes recommendations as to how universities should proceed when a suspicion of academic misconduct exists in order to fairly balance the interests of both universities and students. It highlights the importance of an academic staff member having a preliminary discussion with a student at the stage at which that staff member has a suspicion that a student may be guilty of academic misconduct and is in the process of deciding whether or not to make a formal allegation against the student. In doing so, it examines whether, and to what extent, any procedural fairness requirements apply, or should apply, at this preliminary stage with reference to relevant case law including X v University of Western Sydney (No 3) .